Synthesis, Characterization and Thermal Analysis of a New Acetic Acid (2-Hydroxy-benzylidene)-hydrazide and its Complexes with Hg(II) and Pd(II) - Hajar Sahebalzamani; Shahriare Ghammamy; Shaghayegh Dexhkam; Alireza Hemati Moghadam; Farhod Siavoshifar (E-Journal of Chemistry)
The new complexes have been synthesized by the reaction of Hg(II) and Pd(II) with acetic acid(2-hydroxy-benzylidene)- hydrazide (L). These new complexes were characterized by elemental analysis, IR, H NMR spectroscopy and UV spectral techniques. The changes observed between the FT-IR, H NMR and UV-Vis spectra of the ligands and of the complexes allowed us to establish the coordination mode of the metal in complexes. Thermal properties, TG-DTA of these complexes were studied. TG- DTA and other analytical methods have been applied to the investigation of the thermal behavior and structure of the compounds [M(L)2]Cl2 M= Hg, Pd. Thermal decomposition of these compounds is multi-stage processes.